The little world of Liz Climo. - Climo, Liz (Running Press, 2014)
Climo has charmed her fans with her comic world of whimsical animal characters who grapple with everyday life with wit and humor. This collection features her comics, starring her beloved characters in all kinds of funny situations, from celebrating holidays to helping friends.